Alternative interpretations of the Middle/Upper Paleolithic interface at Vindija Cave (northwestern Croatia) in the context of Central Europe and the Adriatic - Karavanić, Ivor (Array, 2013)
The Paleolithic sites of Croatia are generally situated in two main geographic regions, continental and Adriatic. The most famous sites (Krapina, Vindija, Velika Pećina) are situated in continental area of northwestern Croatia (Hrvatsko Zagorje), which differs geographically and ecologically from the Mediterranean sites situated farther south on the Adriatic coast and its hinterland (Figure 1). Krapina yielded Neandertal remains associated with a Mousterian industry. Unlike Krapina, Vindija and Velika Pećina also contain Upper Paleolithic stratigraphic units and these sites have an important role in the debate on the patterns of Neandertal/early modern human interactions and the Middle/Upper Paleolithic transition in central Europe. Evidence from Vindija were recently discussed in several papers from archaeological, paleoanthropological, geological and genetic perspectives. Different interpretations have been given for determination of lithic industry in level G1, associated with Neanderthal remains. In this paper alternative interpretations of the Middle/Upper Paleolithic transition in Vindija Cave will be presented in the context of central Europe and eastern Adriatic region.